Generalization of the delta-differential autotransformer for 12 and 18-pulse converters - Seixas, FJM; Goncalves, V. A. (IEEE, 2005)
This work proposes a methodology to generalize the A-connections for 12 and 18-pulse autotransformers. A single mathematical expression, obtained through simple trigonometric operations, represents all the connections. The proposed methodology allows choosing any ratio between the input and the output voltages. The converters can operate either as step-up or as step-down voltage. To simplify the design of the windings, graphics are generated to calculate the turn-ratio and the polarity of each secondary winding, with respect to the primary winding. A design example, followed by digital simulations, and experimental results illustrate the presented steps. The results also show that high power factor is an inherent characteristic of multi-pulse converters, without any active or passive power factor pre-regulators needs.